Concurrent and Simultaneous Use of Cannabis and Tobacco and Its Relationship with Academic Achievement amongst University Students - Hernández-Serrano, Olga (Behav Sci (Basel), 2018)
The combined use of cannabis and tobacco is frequent in Europe. Few studies have nonetheless explored this pattern of consumption and its relationship with academic achievement in Spanish population. The aim of the present study was to analyze (1) the frequency of four patterns of polydrug use the last year (non-dual users of cannabis and tobacco; concurrent users: cannabis and tobacco separately; simultaneous users: tobacco in cannabis “joints”; simultaneous users: tobacco in cannabis joints alongside alcohol) by gender and age; (2) grade point average (GPA) by gender and age; (3) the association between the frequency of the four patterns of use and the GPA amongst a sample of 477 Spanish university students. The use of cannabis and tobacco (concurrent and simultaneous) and GPA were assessed by means of self-reported questionnaires. Statistically significant differences were found for the GPA with respect to gender. The GPA by the non-dual users of cannabis and tobacco was significantly higher than the GPA corresponding to the concurrent and simultaneous users. The combined use of cannabis and tobacco, regardless of the type of use (concurrent or simultaneous), is moderately related to poor academic achievement amongst university students.